Heart Signal Acquisition Based System Autoregressive Identification Models (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A system identification (SI) model can be constructed without any prior knowledge of the nature or physics of the relationship that has been involved. It is therefore appropriate to examine the question of (heart rate). In this paper, a simple and efficient hardware design is implemented to acquire the heart signal with the help of several linear models of SI. The relationships between different system identification models are discussed with detailed justification of the aid of these typical types. And then characterize the methods that fit the system structure to measure data input and output, as well as the most basic characteristics of the resulting models. For evaluation, compare between SI models to validate the results.